Dental health in the shadows of global commitments: Addressing neglected priorities in lower middle-income countries - Qamar, Wajiha (Journal of the Pakistan Medical Association, 2024)
I am writing to draw your attention to a serious concern that requires our attention around global health commitments: the frequently disregarded and undervalued dental reforms. In the realm of global health commitments, dental reforms are often ignored and underestimated. (1) Despite significant advancements in many other facets of health owing to these commitments, dental health remains marginalized within its sphere creating a glaring disparity, especially in lower middle-income countries where it’s a crucial concern.(2) Dental health has a significant impact on a person's quality of life in addition to preventing oral diseases. It has a significant impact on a person's quality of life, having an impact on their mental and physical well-being. Neglected oral health can affect speech, self-esteem, and psychosocial wellbeing as well as cause pain, infections, malnutrition, and systemic health problems.(3) The disruptive relationship between oral diseases and significant medical conditions like diabetes, cardiovascular disease, and adverse pregnancy outcomes emphasizes the complex relationship between dental health and overall health. Despite efforts to promote understanding, such as Universal Health Coverage (UHC) and the International Health Regulations (IHR), oral health is often disregarded in global discussion. Particularly in lower middle-income countries, oral health is neglected due to a lack of tailored interventions, which decreases its significance. A significant leap forward has been made with the recent World Health Organization (WHO) resolution that declares oral health a global priority and calls for its inclusion in national strategies. The WHO has acknowledged the need to address this problem immediately.(4) The challenge, however, is recognition into concrete, commitment-backed activities and specific interventions. The resolution has potential, but its effectiveness will be judged by the concrete measures taken to bridge the gaps. The Sustainable Development Goals (SDGs) offer a potential reference point for rectifying this gap. By integrating oral health in SDGs like Goal 3 on excellent health and well-being, a holistic approach may be taken. This integration could help bridge the gap between international commitments, raise the public's awareness of oral health, and foster tailored initiatives for dental reforms. ---Continue